2014
DOI: 10.1016/j.ajog.2014.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Maternal gestational weight gain and offspring risk for childhood overweight or obesity

Abstract: OBJECTIVE The objective of the study was to evaluate the association between gestational weight gain, per the 2009 Institute of Medicine (IOM) recommendations, and offspring overweight/obesity at 2–5 years of age. STUDY DESIGN This was a prospective cohort study of 4145 women who completed a health survey (2007–2009) and subsequently delivered a singleton at Kaiser Permanente Northern California (2007–2010). Childhood overweight/obesity was defined as a body mass index (BMI) z-score of the 85th percentile or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 30 publications
3
126
1
3
Order By: Relevance
“…Based on limited data however correlations between gestational weight gain and offspring birth weight as well as childhood obesity have been demonstrated (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on limited data however correlations between gestational weight gain and offspring birth weight as well as childhood obesity have been demonstrated (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Weight data were collected on 756 women. Only 385 women had weights measured in all three study assessment periods (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) weeks, 20+1 to 32 weeks and >32 weeks gestation) while 427 women had weights measured in Period 3. Individual…”
Section: Introductionmentioning
confidence: 99%
“…The study, however, did not examine gestational weight gain, which is also a risk factor for later childhood obesity independent of prepregnancy BMI. [15][16][17][18] In this study, we aimed to examine the associations among maternal characteristics, prenatal factors-including gestational weight gain-and size, tempo, and velocity. We hypothesized that maternal smoking, parity, and gestational hypertension would be related to infant growth parameters derived using SITAR.…”
Section: Introductionmentioning
confidence: 99%
“…This finding emphasizes the impact that maternal adiposity may have through offspring adiposity on various predictors of subclinical and clinical disease, including diabetes mellitus and cardiovascular diseases. A large US cohort study reported that excessive maternal GWG was independently associated with a 46% increased risk of overweight or obesity in offspring at 2-5 years of age (Sridhar et al 2014). In a retrospective cohort study, excessive maternal GWG had an adverse impact on the risk of childhood overweight and abdominal adiposity (Ensenauer et al 2013).…”
Section: Maternal Prepregnancy Obesity and Gestational Weight Gainmentioning
confidence: 99%